2017
DOI: 10.5115/acb.2017.50.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Histological study on the effect of nicotine on adult male guinea pig thin skin

Abstract: Tobacco smoking has been identified as an important factor in premature skin aging to detect the histological changes occurred in adult male guinea pig thin skin under the influence of low and high doses of nicotine; which constitutes approximately 0.6%–3.0% of the dry weight of tobacco. Fifteen adult male pigmented guinea pigs were equally divided into three groups: group I, control; group IIA, low dose nicotine treated; 3 mg/kg subcutaneously for 4 weeks; and group IIB, high dose nicotine treated; 6 mg/kg su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…This study was designed to evaluate the probable benefit of minocycline on depression-like behaviours and oxidative stress induced by chronic sleep deprivation in mice. The results from the current study depicted that sleep deprivation induced oxidative stress by enhancing production and activity of reactive oxygen species, a mechanism that has been linked to a depression-like phenotype in earlier studies (21,22).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This study was designed to evaluate the probable benefit of minocycline on depression-like behaviours and oxidative stress induced by chronic sleep deprivation in mice. The results from the current study depicted that sleep deprivation induced oxidative stress by enhancing production and activity of reactive oxygen species, a mechanism that has been linked to a depression-like phenotype in earlier studies (21,22).…”
Section: Discussionsupporting
confidence: 66%
“…Photomicrographs were subsequently obtained using a digital camera. Neuronal density or neuronal count was also extrapolated from the photomicrographs as a ratio of viable neuronal cell counts to the square area of the circular view in a section (21).…”
Section: Histology and Estimation Of Neuronal Densitymentioning
confidence: 99%
“…The alteration of collagen metabolism contributes to the slow process of wound healing and this can also contribute to the aging process [ 10 ]. NIC has been linked to premature skin aging and delayed wound healing as a result of nicotine receptors located in keratinocytes of the skin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco smoke causes oxidative stress so that insufficient oxygen is supplied to the skin resulting in tissue ischemia and blood vessel occlusion. 13 Our work showed that pruritus was of gradual onset in 93.3% and progressive course in 44.8% of cases, the mean duration of pruritus was 4.23± 4.9 months. Pruritus was generalized in 73.8% and localized in 26.2%.…”
Section: Discussionmentioning
confidence: 48%